ISLAMIC-BASED COGNITIVE BEHAVIORAL THERAPY TO OVERCOME FUTURE ANXIETY - Syamsul, Rini; Nurjannah, Nurjannah (Universitas Islam Negeri Mataram, 2025)
This research examines the application of Islamic-based Cognitive Behavioural Therapy (CBT) to overcome future anxiety through a literature study. This anxiety is often caused by cognitive distortionssuch as catastrophising and fortune-telling. Findings show that CBT is effective in restructuring negative thought patterns while integrating Islamic values, such as tawakal and prayer, which enrichesthe therapeutic process with a spiritual dimension. Thus, Islamic-based CBT offers a more holistic approach to treating anxiety, combining cognitive and spiritual aspects, especially for Muslimindividuals.